2002
DOI: 10.1016/s0022-5347(05)65381-5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications of Laparoscopic Radical Prostatectomy: The Montsouris 3-Year Experience

Abstract: Laparoscopic radical prostatectomy was performed according to the defined protocol with no complications in 82.9% of patients. The morbidity of this approach compares favorably with that of retropubic surgery. Growing experience and knowledge sharing concerning the prevention and early management of these complications would make possible a further decrease in the morbidity of laparoscopic radical prostatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
125
2
21

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(151 citation statements)
references
References 10 publications
3
125
2
21
Order By: Relevance
“…Guillonneau et al in 2002, in a series of 567 patients, reported that 82.9% did not present complications, stating that this access has lower morbidity than open retropubic surgery (10). Subsequently, the same authors on the following year, now with 1000 patients, concluded that the laparoscopic radical prostatectomy presents satisfactory results concerning tumor control and biochemical recurrence, in addition to being comparable to the open technique in terms of follow-up and results (11).…”
Section: Commentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Guillonneau et al in 2002, in a series of 567 patients, reported that 82.9% did not present complications, stating that this access has lower morbidity than open retropubic surgery (10). Subsequently, the same authors on the following year, now with 1000 patients, concluded that the laparoscopic radical prostatectomy presents satisfactory results concerning tumor control and biochemical recurrence, in addition to being comparable to the open technique in terms of follow-up and results (11).…”
Section: Commentsmentioning
confidence: 98%
“…Some authors have demonstrated that laparoscopic radical prostatectomy provides functional and oncological results that are comparable with the open technique, however with significant decrease in blood transfusion rate, shorter hospital stay and faster recovery (8,10). Guillonneau et al in 2002, in a series of 567 patients, reported that 82.9% did not present complications, stating that this access has lower morbidity than open retropubic surgery (10).…”
Section: Commentsmentioning
confidence: 99%
“…However, LRP requires significant laparoscopic expertise and takes 50-100 cases to be fully mastered. Guillonneau et al [12] reported a mean operative duration of 268 min for the first 50 cases, 245 min for the next 50 and 180 min for the last 350 in a series of 567 patients. In the same series there were 12 conversions to open surgery in the first 50 cases, two in the next 50 and none in the last 467.…”
Section: Feasibility and Learning The Proceduresmentioning
confidence: 99%
“…The rate of rectal injury has been reported to be 0.005-0.5% in open retropubic prostatectomy [18,19]. Guillonneau et al [12] reported rectal injuries in eight of 567 cases (1.4%) in LRP; this can happen during two steps of the procedure, i.e. during incision of the posterior layer of Denonvilliers' fascia if it is not incised close enough to the posterior surface of the prostate, and during apical dissection, when attempting to develop the plane between the rectum and Denonvillier's fascia.…”
Section: Complications Of Lrpmentioning
confidence: 99%
See 1 more Smart Citation